Determinants of entrepreneurial inclination among university students / Mohd Rozaimy bin Ridzuan ... [et al.] - Ridzuan, Mohd Rozaimy; Abd Rahman, Noor Amira Syazwani; Rabun, Mohd Nazir; Ju, Soon Yew; Kong, Lai Kuan (Universiti Teknologi MARA, Pahang, 2021)
Universities play a promising role in encouraging entrepreneurship activities to develop regional and social economies. While the students are studying to survive today's robust business milieu, entrepreneurial cultures and aspirations among them are also shaped. For a university graduate nowadays, wage employment is no longer a guarantee especially in the public sector. Hence, this paper primarily investigates both internal and external determinants that influence the involvement of university students in entrepreneurial activities. Methodologically, this paper utilizes a qualitative study whereby five students whom are involved in entrepreneurial activities are interviewed. The focus is to get their insights about the motivations which engage them in entrepreneurship activities on the campus. Finally, based on the findings, the implications of the study have been forwarded.